2012
DOI: 10.1200/jco.2012.30.15_suppl.1104
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer multifocality-multicentricity and survival outcomes.

Abstract: 1104 Background: Studies have consistently shown a correlation between multifocal (MF) and multicentric (MC) breast cancers and the rate and extent of lymph node metastases, but the literature is divided on whether there is a corresponding impact on survival outcomes. In the absence of compelling evidence to dictate otherwise, the convention according to current TNM staging guidelines has been to stage and treat MF and MC cancers according to the diameter of the largest lesions, without taking other foci of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
1
17
2
Order By: Relevance
“…Due to these confounding factors, it was decided to include TM and age in the multivariant analysis and to exclude multifocality. These results are similar to those reported in a study examining mulitfocality and multicentricity in breast cancer .…”
Section: Resultssupporting
confidence: 90%
“…Due to these confounding factors, it was decided to include TM and age in the multivariant analysis and to exclude multifocality. These results are similar to those reported in a study examining mulitfocality and multicentricity in breast cancer .…”
Section: Resultssupporting
confidence: 90%
“…A more recent study by Lynch et al. included 292 patients who underwent BCT and did not find an association with local recurrence in patients undergoing lumpectomy despite larger and more aggressive tumors in the MF/MC cohort . In our cohort of patients, MF/MC disease was associated with worse LC and DFS regardless of surgery type.…”
Section: Discussioncontrasting
confidence: 52%
“…Studies (35)(36)(37) show that patients with multifocal or multicentric disease have worse disease-free survival rates and higher rates of locally recurrent and metastatic disease. Lynch et al (36) suggested that this may be secondary to larger tumor size, higher histopathologic grade, lymphovascular invasion, and lymph node involvement in patients with multifocal and/or multicentric disease compared with patients with unifocal disease. However, whether a multifocal and/or multicentric tumor is an independent prognostic factor is controversial and currently not considered a part of the TNM staging system (Fig 2).…”
Section: Multifocal and Multicentric Diseasementioning
confidence: 99%